2011
DOI: 10.1111/j.1469-0691.2010.03179.x
|View full text |Cite
|
Sign up to set email alerts
|

Junior doctors' knowledge and perceptions of antibiotic resistance and prescribing: a survey in France and Scotland

Abstract: Our objective was to assess junior doctors' perceptions of their antibiotic prescribing practice and of bacterial resistance. We surveyed 190 postgraduate doctors still in training at two university teaching hospitals, in Nice (France) and Dundee (Scotland, UK), and 139 of them (73%) responded to the survey. The main results presented in this abstract are combined for Nice and Dundee, because there was no statistical difference for these points between the two hospitals. Antibiotic resistance was perceived as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
201
7
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(243 citation statements)
references
References 18 publications
30
201
7
5
Order By: Relevance
“…26,27 Previous studies have found that respondents underestimated the prevalence of resistance, particularly at their own institution. 21,24,25 As noted in previous studies and our study, most healthcare providers believed that excess use of antimicrobials was a cause of resistance, 24,25 but fewer believed that antimicrobials were overused in the hospitals in which they worked. 22,23 Our survey uncovered a substantial knowledge gap which may delay appropriate implementation of transmission precautions and thus facilitate transmission of multidrugresistant organisms.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…26,27 Previous studies have found that respondents underestimated the prevalence of resistance, particularly at their own institution. 21,24,25 As noted in previous studies and our study, most healthcare providers believed that excess use of antimicrobials was a cause of resistance, 24,25 but fewer believed that antimicrobials were overused in the hospitals in which they worked. 22,23 Our survey uncovered a substantial knowledge gap which may delay appropriate implementation of transmission precautions and thus facilitate transmission of multidrugresistant organisms.…”
Section: Discussionmentioning
confidence: 65%
“…22,23,25 As we and others have noted, interactive education appears to be generally preferred to didactic sessions or handouts as reflected in providers' desire for feedback or preference for the advice of local experts and local resources. 21,25 As further evidence of the effectiveness of prescriber audit and feedback, this evidence-based strategy is recommended to improve antimicrobial stewardship. 29 This study had several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations